Rosyjskie życie kulturalno-literackie w Pińsku 1918-1939 - Zienkiewicz, Tadeusz (Acta Polono-Ruthenica, 2007)
For many centuries Pinsk was one of the most important Orthodox centers on Polesie; also in years 1919-1939. In that period, in city lived 11% of Russians (73% of Jews, 16% other nationalities). Russian cultural and literary life was organized by local NGO’s like Russian Benevolent Society or Russian Youth Society. Also, in Pinsk functionated literary club and Russian library. Every year, many activities and cultural events were organized, f.e. Day of Russian Culture, Pushkin Day, Student’s Day. Although the literary environment was small, in Pinsk lived many famous poets and writers, like Wasilij Korotyszewski, Stanisław Mackiewicz. Also the Pinsk cultural life was supported from Warsaw by Dimitri Majkow.